Adrenal Gland Background Findings in CD-1 (Crl:CD-1(ICR)BR) Mice from 104-week Carcinogenicity Studies. (August 2015) - Petterino, Claudio; Naylor, Stuart; Mukaratirwa, Sydney; Bradley, Alys
The authors performed a retrospective study to determine the incidences of spontaneous findings in the adrenal glands of control CD-1 mice. Data were collected from 2, 163 mice from control dose groups in 104-week carcinogenicity studies carried out between 2000 and 2010. Adrenal gland nonproliferative lesions were more common in males than in females. In males, the most common nonproliferative lesions were cortical hypertrophy, cortical atrophy, pigment deposition/pigmentation, cysts, and extramedullary hematopoiesis. In females, the most common nonproliferative lesions were pigment deposition/pigmentation, extramedullary hematopoiesis, and cortical atrophy. Proliferative lesions were more common in females than in males. In both sexes, the most common proliferative lesions were subcapsular cell hyperplasia, focal cortical hyperplasia, and subcapsular cell tumor. Pheochromocytomas were uncommon in both sexes, with a slightly higher incidence in females, and the benign type was more frequent than the malignant type. Lymphoma was the most common metastatic tumor in both males and females, followed by histiocytic sarcoma and erythroid/myeloid leukemia. To the best knowledge of the authors, there are no recent reports on spontaneous pathological findings in the adrenal glands of CD-1 mice, and these results will facilitate the interpretation of background findings in carcinogenicity studies.